Environmentally Based Strategic Management in the Management of Non-Communicable Diseases by the Magelang City Health Office, Indonesia - Dewi, Alif Puspita; Saharuddin, Erni (Jurnal Pemerintahan dan Kebijakan (JPK), 2025)
This study aims to identify and analyze the environmental-based strategic management implemented by the Magelang City Health Office in the management of non-communicable diseases (NCDs). Non-communicable diseases cause 74% of global deaths (approximately 41 million people per year), thus requiring comprehensive and sustainable management. The method used was descriptive qualitative with data triangulation (observation, interviews, documentation). The scientific contribution of this research lies in the integration of strategic management theory according to Hunger and Weelen (environmental completion and evaluation) with strategic theory according to Kotten and Salusu, which complement each other in the context of regional health policy, especially in facing the complexity of implementing NCD control at the local level. The research results show that the NCD management strategy in Magelang City is comprehensive, encompassing organizational strategies, programs, resources, and institutions, while remaining grounded in environmental monitoring. Efforts to promote health and early screening, involve cadres, and coordinate across sectors have been implemented. However, screening success remains hampered by low public participation due to busy schedules and the spread of hoax news. The Health Office has responded through an educational approach, involving cadres, and strengthening multisectoral collaboration as a form of seriousness in addressing the challenges of NCDs.